2002
DOI: 10.1089/10507250252949469
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Thyroxine Administration Protects the Heart in a Pattern Similar to Ischemic Preconditioning

Abstract: We have previously shown that long-term thyroxine administration can protect the heart against ischemia. In the present study, we investigated whether thyroxine-induced cardioprotection can mimic the pattern of protection that is afforded by a well-established cardioprotective means such as ischemic preconditioning. In a Langendorff-perfused rat heart preparation, after an initial stabilization, normal and thyroxine-treated hearts were subjected to 20 minutes of zero-flow global ischemia followed by 45 minutes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0
14

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(75 citation statements)
references
References 15 publications
2
59
0
14
Order By: Relevance
“…Ischemic preconditioning attenuated ischemia-induced reciprocal changes in COX I and COX III levels (59). Moreover, chronic administration of thyroid hormone affected COX I and III expression (46) and protected the heart against lethal ischemic injury (38). In line with these reports, the present study demonstrates increased COX I and decreased COX III gene expression and the improved cardiac ischemic tolerance in SHRCd36.…”
Section: Discussionsupporting
confidence: 87%
“…Ischemic preconditioning attenuated ischemia-induced reciprocal changes in COX I and COX III levels (59). Moreover, chronic administration of thyroid hormone affected COX I and III expression (46) and protected the heart against lethal ischemic injury (38). In line with these reports, the present study demonstrates increased COX I and decreased COX III gene expression and the improved cardiac ischemic tolerance in SHRCd36.…”
Section: Discussionsupporting
confidence: 87%
“…Buser et al (1990) showed that isolated hyperthyroid rat hearts displayed postischemic functional recovery comparable with euthyroid hearts, whereas hypertrophied hearts from rats with pressure overload due to aortic banding recovered poorly. Pantos et al (1999Pantos et al ( , 2000Pantos et al ( , 2002 showed enhanced postischemic functional recovery in hyperthyroid rat hearts, associ-CARDIOPROTECTION AND RISK FACTORS ated with earlier and greater peak contracture than normal hearts, a consistent feature of global ischemia models of ischemic preconditioning. Interestingly, the effect on contracture seen in hyperthyroid hearts was additive to that of ischemic preconditioning (Pantos et al, 2001).…”
Section: B Experimental Ischemia/reperfusion Injury In Left Ventricumentioning
confidence: 73%
“…Organ preconditioning by these hormetic agents is not restricted to the liver [26][27][28] , considering that (1) thyroid 1) thyroid ) thyroid hormone-induced preconditioning against IR injury is also observed in the heart [95,96] , with a pattern of protection comparable to that of ischemic preconditioning [97] ; (�) beneficial effects of n-3 LCPUFA have been dem-�) beneficial effects of n-3 LCPUFA have been dem-) beneficial effects of n-3 LCPUFA have been demonstrated in rheumatoid arthritis, inflammatory bowel disease, coronary artery disease, asthma and sepsis, conditions with inflammation as a key component of their pathology [48] , in addition to neuroinflammation in all major central nervous system diseases [98] ; and (�) protec-�) protec-) protective effects of iron are reported in cardiomyocytes and heart [99][100][101] , oligodendroglia cells [102] and neurones [10�] . T�, n-3 LCPUFA or iron liver preconditioning are suitable to be introduced in the clinical setting, considering that these hormetins are known to be well tolerated in the treatment of hypothyroidism [104] , non-alcoholic fatty liver disease [72][73][74][75][76] and other diseases [48] , or anemia [105,106] , respectively.…”
Section: Discussionmentioning
confidence: 99%